PENGARUH METODE LATIHAN DRILL TERHADAP AKURASI PUKULAN FOREHAND TENIS LAPANG DI BAYUNING TENIS CLUB - Ridhawa Kusumah; Ramdhani Rahman (STKIP Subang, 2025)
Ridhawa Kusumah (NIM 212223059) Pengaruh Metode Latihan Drill Terhadap Akurasi Pukulan Forehand Tenis Lapang Di Bayuning Tenis Club. This study aims to determine the effect of the Drill Training Method on the Accuracy of Tennis Forehand Shots at Bayuning Tennis Club. The research method used was an experiment with a one-group pretest-posttest design. The subjects were 15 Bayuning Tennis Club athletes who participated in a 6-week training program, consisting of 18 sessions, with three sessions per week. The data collection instrument used was the Hewwit Tennis Accuracy Test. The results showed a significant increase in forehand accuracy, with an average pretest score of 26.5, increasing to 39.6 in the posttest. The paired sample t-test obtained a significance value of 0.000 <0.05, indicating a significant effect of drill training on tennis forehand accuracy. Thus, this training method has proven effective in improving basic forehand skills in tennis.